Short-stem reconstruction for megaendoprostheses in case of an ultrashort proximal femur - Dieckmann, Ralf (BioMed Central, 2014)
BACKGROUND: Tumors of the distal femur and diaphysis with proximal metaphyseal extension into the femur present a challenge for limb salvage. The conventional treatment consists of limb salvage with total femur replacement. This case study aims to present preliminary results and experience with short-stem reconstruction, focusing on the mechanical stability of the procedure. METHODS: Sixteen short stems were implanted in 15 patients. The patients’ mean age was 33,3 years (range 11–73). In 10 patients, the stem was used for distal femur reconstruction, in one patient for diaphyseal reconstruction, and in four for a stump lengthening procedure. All of the patients had a primary sarcoma in their history. The mean follow-up period was 37 months (range 5–95 months). The clinical and functional follow-up data were analyzed. RESULTS: Ten patients (67%) were still alive at the time of evaluation. Three complications associated with the stem were noted. In one case, there was aseptic loosening after 58 months; in another, aseptic loosening occurred because the diameter of the stem had initially been too small; and in one case, there was breakage of the fixation screw, without any clinical symptoms. The average Musculoskeletal Tumor Society score for all patients was 23 (range 9–28). The mean result for the distal femur replacement was 24 (range 22–28). None of the surviving patients with distal femur replacements needed any crutches or had a Trendelenburg limp. Both living patients who underwent a stump lengthening procedure were able to walk with an exoprosthesis. CONCLUSIONS: The short stem is a good solution that can prevent or delay proximal femur resection in patients with tumors extending into the proximal metaphyseal femur. Additional risks of proximal femur resection, such as dislocation, opening of another oncological compartment, Trendelenburg limp, and chondrolysis can be avoided.